A Study of Modern Indian Cosmetic Products’ Advertisements with special reference to the Sadharanikaran Model of Communication - Chaudhury , Sumedha (Bodhi: An Interdisciplinary Journal, 2024)
This article presents a study of modern Indian cosmetic products’ advertisements taking Adhikary’s Sadharanikaran Model of Communication (SMC) as a theoretical framework. In this context, a content analysis through YouTube Channels was carried on first three Indian cosmetic companies’ advertisements published by F6S Community on June 27, 2024, and another first three Indian cosmetic companies or brands published by Cashaly on March 20, 2024.The attempt to relate the SMC was seen as a finding in the research work through the languages, colours, gender, comments and views of the chosen advertisements on their YouTube Channels.